2010
DOI: 10.1111/j.1349-7006.2010.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Bmi‐1 is related to proliferation, survival and poor prognosis in pancreatic cancer

Abstract: B‐cell‐specific Moloney murine leukemia virus insertion site 1 (BMI1) is a member of the polycomb group of transcriptional repressors. Until now, its expression and functional significance in pancreatic carcinogenesis was unknown. In the present study, we demonstrated that expression of BMI1 was markedly up‐regulated in pancreatic cancer cell lines and surgically resected cancer specimens. In addition, BMI1 expression levels correlated positively with the presence of lymph node metastases and negatively with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 44 publications
9
63
1
1
Order By: Relevance
“…Previous studies have also suggested that Bmi-1 is associated with the protection of tumor cells from apoptosis (31,32). Moreover, the increased expression of Bmi-1 in certain tumors correlates with a poor prognosis (20,32,33). Additionally, increasing evidence indicates that the RNAi-mediated depletion of Bmi-1 can sensitize tumor cells to chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also suggested that Bmi-1 is associated with the protection of tumor cells from apoptosis (31,32). Moreover, the increased expression of Bmi-1 in certain tumors correlates with a poor prognosis (20,32,33). Additionally, increasing evidence indicates that the RNAi-mediated depletion of Bmi-1 can sensitize tumor cells to chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been found to be essential for the self-renewal of normal and malignant stem cells (15). Several lines of evidence have also indicated that Bmi-1 is extensively upregulated in a variety of malignancies, including non-small cell lung cancer (16), leukemia (17), as well as breast (18), colorectal (19), pancreatic (20) and prostate cancer (21). Moreover, it has been demonstrated that Bmi-1 is overexpressed in MM and can regulate the growth and clonogenic capacity of MM cells both in vitro and in vivo (22).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have demonstrated that BMI1 serves important functions in a number of biological processes, including the cell cycle, apoptosis, senescence and proliferation (33)(34)(35). In pancreatic cancer, BMI1 is upregulated and expression levels of BMI1 are associated with proliferation, survival and poor prognosis of patients with pancreatic cancer (36). Furthermore, BMI1 functioned as an oncogene in pancreatic cancer by promoting chemoresistance, invasion and tumorigenesis of pancreatic cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of BMI-1 in gastric and breast cancer has been identified to promote cell growth and proliferation, inhibit apoptosis and enhanced clone formation capability (6,21,22). By contrast, the depletion of BMI-1 in certain pancreatic cancer cell lines was found to suppress cell proliferation, sensitize apoptosis and inhibit tumor formation in nude mice (13,(23)(24)(25). In addition, upregulation of BMI-1 expression enhanced the ability of colony formation in a soft agar assay in non-small cell lung cancer (NSCLC) tissues (26).…”
Section: Bmi-1 and Cancermentioning
confidence: 99%
“…For instance, Song et al investigated the survival of 72 patients with pancreatic cancer and identified that the overexpression of BMI-1 was associated with a significantly reduced overall survival (24). In addition, Yang et al studied the BMI-1 expression and survival in a cohort of 179 patients with invasive ovarian carcinoma (9).…”
Section: Bmi-1 and Cancermentioning
confidence: 99%